Impact of Brick Kilns’ Emission on Soil Quality of Agriculture Fields in the Vicinity of Selected Bhaktapur Area of Nepal - Gunjan Bisht; Sanjila Neupane (Applied and Environmental Soil Science)
The study was conducted to evaluate soil quality and impact of brick kiln on different physicochemical parameters of soils of agricultural field, located in the vicinity of Bhaktapur, Nepal. The study was carried out by determining the physicochemical characteristics of soil, soil fertility, and heavy metal contamination of soil. During the entire study period, water absorptivity of soil ranged from 2.4 to 3.3 mg/L, pH varies from 5.885 to 7.64, and organic carbon content and organic matter varied from 0.277 to 0.93%, from 0.477% to 1.603%, respectively. Nutrient content, that is, sulfate and nitrate concentration, in the soil ranged from 0.829 to 3.764 mol/L and from 0.984 to 29.99 mol/L, respectively. The findings revealed that concentrations of heavy metals (chromium and lead) were within permissible limit, although the levels were higher in soil at 50 m and decrease farther from brick kiln. However, the physical parameters and nutrient content were deficient in soil at 50 m while increasing gradually at distances of 100 m and 150 m. The variation of result obtained for physical parameters supports the fact that quality of soil in terms of heavy metal content and nutrient content was directly proportional to the distance from the kiln; that is, the quality of soil increased with increasing distance.